Ghulam Sinan’s Commentary on al-Risala al-Fathiyya - Orhan Güneş (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
Some of the scholars who were left without a patron due to the assassination of Ulugh Beg (d. 1449), the founder of the Samarqand Madrasa and Observatory, migrated to Anatolian lands. Scholars including Fatḥallāh al-Shirwānī (d. 1486) and ʿAlī Qūshjī (d. 1474) carried the Samarqand astronomical tradition to these lands. ʿAlī Qūshjī, who served as a scholar at the Ṣaḥn-i Thamān and Ayasofya madrasas, trained many students in what can be considered a short period of time and helped theoretical astronomy gain momentum in Ottoman lands. Among these students was Ghulām Sinān (d. 1506-7). Ghulām Sinān wrote a commentary on his teacher’s work, which he had written under the title al-Risāla al-Fatḥiyya during his tenure as a scholar. This commentary, which Ghulām Sinān wrote under the title Fatḥ al-Fatḥiyya, is one of two extant commentaries on al-Risāla al-Fatḥiyya. The work is important not only because it is a commentary on one of the first theoretical astronomical works written in the Ottoman Empire, but perhaps more importantly because it conveys detailed testimonies about the teacher–student relationship of the period and about how lessons were actually taught. This approach, which is uncommon in the history of science, makes this work very important. The main purpose of this paper is not to explain the theoretical issues covered in the work, even if they are mentioned due to the subject. Rather, the focus of the study is on Ghulām Sinān’s relationship with his teacher ʿAlī Qūshjī, which sometimes involved intellectual arguments and disagreements. In addition, through references to various individuals and books, an attempt is made to reveal the sources Sinān was drawing from.